The battle for the Arab Spring : revolution, counter-revolution and the making of a new era - Noueihed, Lin; Warren, Alex (Yale University Press, 2012)
Sparked by the protest of a single vegetable seller in Tunisia, the flame of revolutionary passion swept across the Arab world in what has come to be called the Arab Spring of 2011. Millions took to the streets in revolt: the governments of Tunisia, Egypt, and Libya fell, other regimes remain embattled, and no corner of the region has escaped unchanged. In this informed and accessible book, Lin Noueihed and Alex Warren explain the economic and political roots of the Arab Spring, assess what has been accomplished so far, and consider the many stumbling blocks that confront the Arab nations as they try to shape their futures. Through research, interviews, and a wealth of firsthand experience, the authors explain the unique set of obstacles that endanger stability in each country. They analyze the challenges many Arab nations face in building democratic institutions, finding consensus on political Islam, overcoming tribal divides, and satisfying an insatiable demand for jobs. In an era of change and uncertainty, this insightful guide provides the first clear glimpse of the post-revolutionary future the Arab Spring set in motion.